2012
DOI: 10.2176/nmc.52.652
|View full text |Cite
|
Sign up to set email alerts
|

Nontraumatic Cervical Disc Herniation in a 21-Year-Old Patient With No Other Underlying Disease

Abstract: A 21-year-old woman presented with cervical myelopathy due to nontraumatic cervical disc herniation associated with cervical canal stenosis. The patient underwent removal of the herniated disc and anterior fusion with an autogenous iliac crest bone graft. After surgery, the patient showed satisfactory improvement. Cases of cervical disc herniation in our center and reported cases without cervical trauma in either young adults or in childhood were reviewed retrospectively. We discuss the pathogenesis of cervica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…[13,[21][22][23][24] Furthermore, cervical disc herniation is usually seen in cases aged >40 years, different from lumbar disc herniation. [25,26] Adams et al [27] showed that cadaveric discs aged >50 years are damaged even by minor traumas.…”
Section: Discussionmentioning
confidence: 99%
“…[13,[21][22][23][24] Furthermore, cervical disc herniation is usually seen in cases aged >40 years, different from lumbar disc herniation. [25,26] Adams et al [27] showed that cadaveric discs aged >50 years are damaged even by minor traumas.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients with herniated discs may have no clinical symptoms [4]. Ikeda H. et al (2012) described a case of formation of a herniated cervical intervertebral disc with stenosis of the spinal canal and the development of a symptom of myelopathy, which was eliminated by surgical placement [5].…”
Section: Introductionmentioning
confidence: 99%